Optimalisasi pembelajaran salat dan peningkatan kemandirian pada Siswa Tunagrahita Tingkat SMP di SLB Negeri Salatiga - Sundari, Yesi Ika; Syamsiyah, Barid (Journal of Smart Education and Learning, 2024)
This study aims to describe the development of prayer skills and independence of mentally retarded students at the junior high school level at SLB Negeri Salatiga in the 2023/2024 academic year, as well as the supporting and inhibiting factors. This study uses a descriptive qualitative method with data obtained through interviews, observations, and documentation. The study's results indicate that prayer skills are developed through teaching content, practical exercises, congregational prayers, murojaah, kultum (religious lecture)), and dhikr. Indicators of success include student attendance at the prayer room, the ability to perform and sequence prayer movements correctly, and aligning readings and movements. Independence is developed through the Good Practice and Positive Culture program, vocational learning, and self-development. Indicators of student independence include physical and social abilities and independent initiatives. Supporting factors for prayer development include support from Islamic Religious Education teachers, involvement of friends and parents, and complete facilities, while obstacles include limited students and time. Supporting factors for developing independence include support from teachers and facilities, while obstacles are the varying levels of student intelligence.